Thermo-mechanical assessment of high entropy (Fe-Ni-Cx (X=0.3-0.5), (Fe-Cr-Cx (X=0.3-0.5) ternary alloys system using calphad method - Waseem Ullah shah; Dil faraz khan khan; haiqing yin yin; saeed ullah jan jan (Kuwait Journal of Science)
The thermodynamical assessment of high entropy alloys (Fe-Ni-Cx (X=0.3-0.5)), (Fe-Cr-Cx (X=0.3-0.5)) system is performed in this research work through Fe-demo database and Thermo-Calc software package. The high energy thermal analysis is manipulated for yield strength from FCC to BCC, precipitation from cementite to M7C3 (grain boundaries), Crack Susceptibility Coefficient for Fe-Ni-C ,Fe-Cr-C ternary alloys system at (1900-3000)K temperature with constant atmospheric pressure of 106 Pascal. The highest crack susceptibility coefficient for Fe-Cr-C, Fe-Ni-C system is found 2.70, 2.60 with mass percent of C 0.11%, at 3000K of temperature with Mass percent. Yield strength from FCC to BCC is found 798 MPa, 36 MPa for Fe-Cr-C, Fe-Ni-C ternary alloys at the cost of 2.2, 0.1 mass% C. Phase transition is noted from cementite to M7C3 at 1346.77339 K. FCC_A1#3 phases with 0.98772 moles and 0.01228 mole Of M7C3 with 0 moles of M23C6 carbide phases observed. The comprehensive line investigation of mechanical properties is justified with simulation/computational inputs. The results are feasible for industrial sectors and metallurgical centers for operation. The alloy shows equilibrium and good stability.